Neuropathy in the setting of alcoholism-an entity less thought of - Paneyala, Shasthara; C., Nemichandra S.; Sundaramurthy, Harsha; Colaco K., Vimala Christina (International Journal of Research in Medical Sciences, 2020)
Disulfiram is a commonly used adjunctive treatment in the management of alcohol dependency. It has been noted that disulfiram can induce peripheral neuropathy, the mechanism of which has not been clearly determined. A 35-year-old patient, reformed alcoholic, on disulfiram presented with complaints of painful distal dysesthesias and foot drop. Clinical examination revealed bilateral foot drop without any objective sensory loss. Patient was evaluated for the same and routine blood investigations including vitamin B-12, inflammatory and virological markers were found to be normal. Nerve conductions studies revealed in excitable bilateral common peroneal and tibial nerves. Possibility of disulfiram induced peripheral neuropathy was thought of and drug was withdrawn. Patient was followed up and after two months improvement in motor power and reduction in paraesthesia’s was noted. Disulfiram is a commonly used drug, the uncommon side effect of which is distal predominant axonal neuropathy. This must be kept be kept in mind when evaluating a patient presenting with features of peripheral neuropathy, on a background of alcohol abuse.